Aligning Instruction with Learner Preferences: Listening Comprehension Strategies of Low-Achieving Students in an Indonesian High School - Mufidah, Isroul Mumtazil; Yunus, Muhammad; Heriyawati, Dwi Fita; Subarjo, Subarjo (Universitas Cokroaminoto Palopo, 2026)
This research explores the preferences and strategies employed by low-achieving students in listening comprehension at SMA An-Nur Bululawang Malang. Using a qualitative descriptive design, data were collected through semi-structured interviews, classroom observations, and documentation involving four 11th-grade students identified as low achievers. The findings reveal that listening difficulties are primarily caused by fast speech, limited vocabulary, accent variation, and lack of exposure outside the classroom. Despite these challenges, students demonstrated adaptive strategies: cognitive approaches such as repetition and note-taking, socio-affective practices like group discussion and peer support, technology-based tools including podcasts, songs, and subtitles, as well as teacher-supported methods such as classroom repetition and guided discussion. Their preferences varied from individual listening with subtitles, collaborative group activities, multimedia resources, to structured classroom repetition, reflecting diverse learning needs. Collectively, the research highlights the importance of aligning instructional practices with learners’ preferences and coping strategies to foster engagement, confidence, and improved listening comprehension. The results suggest that flexible, learner-centered approaches integrating traditional repetition, collaborative learning, and digital resources can better support low-achieving students in developing listening competence.